Development and validation of the first brazilian french-based asphalt mix complex modulus and fatigue test apparatus - Barra, Breno; Momm, Leto; Guerrero, Yader; Brosseaud, Yves; Momm, Gustavo (Transportes, 2020)
The main aim of this paper is to present the development and validation procedures of the first brazilian french-based asphalt mix complex modulus and fatigue test apparatus, so-called FADECOM, in order to demonstrate the effective application of the results obtained in pavement design procedures. Magnetic sensitive Hall Effect non-contact captors determine amplitude displacement, while loading cells capture force amplitude by a diaphragm system. Independent cooling and heating chambers assure a precise temperature control comprising a range from -30ºC to above 100ºC with an accuracy of 0.1ºC. A frequency inverter controls the emission of pulses usually set from 1Hz to 30Hz. For validating the apparatus, a scientific cooperation agreement was dealt with French Institute of Transportation Sciences and Technologies, Development and Road Network (IFSTTAR), in which specimen samples were tested in both UFSC and IFSTTAR laboratories. The crossed-results obtained indicate an excellent performance and accuracy of FADECOM apparatus, presenting variations around just 3 microstrains in determining fatigue strains at 106 cycles (e6) and less than 10% related to the complex stiffness modulus, demonstrating huge accuracy of the FADECOM apparatus and its practical feasibility to be applied in pavement design procedures, based on the technical principles of French methodology.